2021
DOI: 10.3390/nano11123351
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Absorption and Refraction of Picosecond and Femtosecond Pulses in HgTe Quantum Dot Films

Abstract: We report measurements of the saturated intensities, saturable absorption, and nonlinear refraction in 70-nm thick films containing 4 nm HgTe quantum dots. We demonstrate strong nonlinear refraction and saturable absorption in the thin films using tunable picosecond and femtosecond pulses. Studies were carried out using tunable laser pulses in the range of 400–1100 nm. A significant variation of the nonlinear refraction along this spectral range was demonstrated. The maximal values of the nonlinear absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies of the nonlinear refraction and absorption in other mercury-contained QDs (HgTe, HgSe) have shown that those species demonstrate smaller nonlinear refractive indices and nonlinear absorption coefficients compared with the HgS QDs [20,29]. Moreover, HgS QDs have demonstrated the efficient THG, which was not reported during the studies of HgTe and HgSe QDs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies of the nonlinear refraction and absorption in other mercury-contained QDs (HgTe, HgSe) have shown that those species demonstrate smaller nonlinear refractive indices and nonlinear absorption coefficients compared with the HgS QDs [20,29]. Moreover, HgS QDs have demonstrated the efficient THG, which was not reported during the studies of HgTe and HgSe QDs.…”
Section: Discussionmentioning
confidence: 94%
“…The thin films were prepared by layer-by-layer deposition using the dip-coating on a 0.15 mm-thick glass substrate. The ligand shell exchange by 1,2-ethanedithiol (EDT) has been done using 1:1:100 EDT/HCl/2-propanol solution [20]. The glass substrate was withdrawn at a speed of 18 mm/min.…”
Section: Preparation and Characterization Of Samplesmentioning
confidence: 99%
“…As a result of the sustained efforts of scientists to discover SA materials with valuable properties, such as the semiconductor saturable-absorber mirror (SESAM) [ 11 , 12 ], many two-dimensional (2D) layered materials have now been considered as alternative systems [ 13 , 14 , 15 , 16 ]. 2D materials are characterized by their chemical diversity and structural complexity, as well as their unique optical and magnetic properties [ 17 , 18 , 19 ]. Moreover, semiconductor materials with direct band gaps have become important in a range of technologies such as solar cells and lasers.…”
Section: Introductionmentioning
confidence: 99%